ANALISIS ATRIBUT APA SAJA YANG HARUS DIPERTAHANKAN DAN DITINGKATKAN KINERJANYA DI RUMAH MAKAN AYAM GEMPREK MAS BOY DI KOTA BANDAR LAMPUNG - Bunga Ambar Tiara; Agus Hudoyo; Lina Marlina (Lampung University, 2023)
The service performance of a restaurant is important in maintaining customers. This study aims to analyze the service attributes that need to be maintained and improved in the performance of the restaurant. This research is located at the Rumah Makan Ayam Geprek Mas Boy in Bandar Lampung. Data collection was carried out in May - June 2022. The importance and performance of the restaurant attributes were scored on a Likert scale. Data collection uses a questionnaire that has been tested for validity and reliability. The number of samples in this study was 60 respondents. The research method used was a survey method and the determination of the research location was carried out purposively. The analytical method used is the Importance Performance Analysis (IPA) method. There are 18 attributes studied and divided into 3 groups, namely product, attention, and facilities. The results of the research showed that there are 18 attributes that are considered important by consumers. There are 16 attributes that are considered to satisfy the consumers of Rumah Makan Ayam Geprek Mas Boy. There are 10 attributes that need to be maintained at the Rumah Makan Ayam Geprek Mas Boy. Key words: attributes, importance, perfomance